2017
DOI: 10.1016/j.surfcoat.2017.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of the mechanical and optical properties of Ca-Si-O-N thin films deposited by RF magnetron sputtering

Abstract: Ca-Si-ON thin films were deposited on commercial soda-lime silicate float glass, silica wafers and sapphire substrates by RF magnetron co-sputtering from Ca and Si targets in an Ar/N 2 /O 2 gas mixture. Chemical composition, surface morphology, hardness, reduced elastic modulus and optical properties of the films were investigated using X-ray photoelectron spectroscopy, scanning electron microscopy, nanoindentation, and spectroscopic ellipsometry. It was found that the composition of the films can be controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The thin films in Mg-Si-O-N system have higher content of N and Mg as compared to the bulk glass prepared by melt quenching or sol-gel techniques in the same system[12,24]. The high nitrogen content in the Mg-Si-O-N thin films as compared to the Ca-Si-O-N thin films[11] prepared under similar conditions might be due to the high affinity of Mg towards nitrogen. A similar trend has been observed in bulk Mg/Ca-Si-O-N glasses[12].…”
mentioning
confidence: 93%
“…The thin films in Mg-Si-O-N system have higher content of N and Mg as compared to the bulk glass prepared by melt quenching or sol-gel techniques in the same system[12,24]. The high nitrogen content in the Mg-Si-O-N thin films as compared to the Ca-Si-O-N thin films[11] prepared under similar conditions might be due to the high affinity of Mg towards nitrogen. A similar trend has been observed in bulk Mg/Ca-Si-O-N glasses[12].…”
mentioning
confidence: 93%
“…Oxynitride glasses prepared via sol-gel methods are also comparatively more transparent, and silicon-free oxynitride glasses, e.g., P-O-N based, are in contrast transparent. Recently, Sharafat et al [23][24][25] The obtained glasses were examined by X-ray powder diffraction (XRPD), using a Panalytical X'pert PRO MPD diffractometer and CuK α1 radiation. Samples were analysed by light microscope and scanning electron microscopy to observe the surface morphology.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, silicon-free oxynitride glasses, e.g., P−O−N-based, and oxynitride glasses prepared via sol–gel methods are transparent. Recently, Sharafat et al [ 23 , 24 , 25 ] have reported amorphous transparent thin films in the nitrogen enrich Mg/Ca−Si−O−N systems prepared by reactive RF magnetron co-sputtering from Mg/Ca and Si targets in an N 2 /O 2 /Ar gas mixture. These thin films are free from elemental silicon and metallic silicides impurities, as found in bulk Mg/Ca−Si−O−N systems and contain an unprecedented amount of modifier and nitrogen.…”
Section: Introductionmentioning
confidence: 99%